Laws of Radiation Grafting of Styrene to PVDF Films and Characterization of the Grafted Polymer; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Sokhoreva V. V. Valentina Viktorovna; Golovkov V. M. Vladimir Mikhailovich; Dubrova N. A. Nataliya Aleksandrovna; Sidko D. (Materials Science and Technologies, 2015)
Title screen